2020
DOI: 10.1101/2020.12.15.422832
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

DRAM1 requires PI(3,5)P2generation by PIKfyve to deliver vesicles and their cargo to endolysosomes

Abstract: Endolysosomal vesicle trafficking and autophagy are crucial degradative pathways in maintenance of cellular homeostasis. The transmembrane protein DRAM1 is a potential therapeutic target that primarily localises to endolysosomal vesicles and promotes autophagy and vesicle fusion with lysosomes. However, the molecular mechanisms underlying DRAM1-mediated vesicle fusion events remain unclear. Using high-resolution confocal microscopy in the zebrafish model, we show that mCherry-Dram1 labelled vesicles interact a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 50 publications
(75 reference statements)
1
2
0
Order By: Relevance
“…Finally, using an mCherry-Dram1 construct [ 38 ], we demonstrated that Dram1 colocalizes with A. fumigatus conidia in phagocytes ( Figure 5(g )), supporting the conclusion that this autophagy-stimulating factor contributes to the response of phagocytes to A. fumigatus .…”
Section: Resultssupporting
confidence: 71%
See 2 more Smart Citations
“…Finally, using an mCherry-Dram1 construct [ 38 ], we demonstrated that Dram1 colocalizes with A. fumigatus conidia in phagocytes ( Figure 5(g )), supporting the conclusion that this autophagy-stimulating factor contributes to the response of phagocytes to A. fumigatus .…”
Section: Resultssupporting
confidence: 71%
“…It has recently been reported that microbial-targeted autophagy (xenophagy) and its related process LAP contribute to efficient intracellular fungal clearance by innate immune cells in vitro [ 22–24 ]. To visualize the in vivo autophagy activation dynamics in innate immune cells after A. fumigatus phagocytosis, we imaged the fluorescent map1lc3b /Lc3b reporter zebrafish line Tg(CMV:EGFP -map1lc3b ) zf155 [ 37 ] or Tg( bactin : mCherry- map1lc3b ) [ 38 ] – further referred to as GFP-Lc3 and mCherry-Lc3, respectively – by confocal microscopy shortly after infection. These transgenic lines allow the study of autophagy-related dynamics in real time by analyzing the accumulation of fluorescently labeled Lc3b in specific vesicles ( Figure 2 , Movie S2).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation